Histology-driven tailoring of surgical approaches in retroperitoneal soft tissue sarcoma: retrospective cohort study - Musa, Julian; Willis, Franziska; Rompen, Ingmar F.; Harnoß, Julian-Camill; Grünewald, Thomas G. P.; Saeedi, Mohammed al; Büchler, Markus W.; Schneider, Martin (BJS open, 2025)
Histology-driven tailoring of surgical approaches for retroperitoneal soft tissue sarcoma is currently under debate. Compelling evidence assessing the role of histology-dependent extent of resection is lacking. The aim of this study was to assess outcomes of patients with primary retroperitoneal liposarcoma (LPS) or leiomyosarcoma (LMS) according to whether comprehensive (formerly ‘compartmental’) resection (CR) was performed.A retrospective study was conducted on data from patients undergoing surgical resection for LPS and LMS at Heidelberg University Hospital (2002-2019). Parameters were compared between groups with and without CR, with subgroup analyses for grading (LPS). Kaplan-Meier and Cox regression analyses were used to identify predictors of disease-specific survival (DSS), local recurrence-free survival, and distant metastasis-free survival.In total, 119 patients with primary LPS and 46 patients with primary LMS were identified. DSS was improved in patients with LPS with CR (P = 0.049), and both DSS (P = 0.040) and distant metastasis-free survival (P = 0.041) were improved in the subgroup of patients with primary G3 LPS. In contrast, CR in patients with LMS was not associated with improved DSS, local recurrence-free survival, or distant metastasis-free survival. CR was associated with more severe postoperative complications (P = 0.021) and a longer hospital stay (P = 0.013) in patients with LPS, longer operation times (P < 0.010) in both patients with LPS and LMS, and increased blood loss (P = 0.008) in patients with LMS.CR is associated with improved DSS in patients with primary LPS, which is not the case in patients with primary LMS. Given the association between CR and increased perioperative morbidity, surgical strategies for retroperitoneal soft tissue sarcoma should be individualized according to the underlying histology.